PENGARUH PENGGUNAAN MEDIA FLASH CARD TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS III SDN 188 PEKANBARU - Lydia Emilsa; Guslinda Guslinda (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
The background of this research is the low level of narrative essay writing skills. This is due to several factors including because students are less interested and feel bored with writing material, students have difficulty in choosing words and use of spelling, it is because students do not have a broad vocabulary, so the words used are just that, so essays written only modest, usually consisting of 1-2 sentences. Then students are less skilled in connecting one sentence with another sentence so that no good paragraphs are formed. Students are confused in placing punctuation marks such as periods, commas, question marks, and exclamation points that are still incorrect. This study aims to determine the effect of the use of flash card media on the narrative essay writing skills of third grade students at SDN 188 Pekanbaru. This research method uses quasi experimental Nonequivalent Control Group Design. The population of this research is class III students of SDN 188 Pekanbaru, which is class IIIA, amounting to 40 students as the control class and class IIIB, which amounts to 40 students as the experimental class. The sampling technique uses saturated samples. The instrument used as data in this study was an essay test in the form of a narrative essay writing assignment. Hypothesis testing is done by using the "t" test and Effect Size (ES). Based on the results of the study shows that the use of flash card media affects the writing skills of students' narrative essays and the magnitude of the effect of flash card media is included in the medium category